Inequality in distribution of human resource in health sector: case study of dentists in Fars province - Somayeh Moalemi; Zahra Meshkani; Seyed Masood Moosavi Nejad; Neds Valipour yekani (Kerman University of Medical Sciences, 2018)
Inequality in Distribution of Human Resource in Health Sector: Case Study of Dentists in Fars Province   Moalemi Somayeh1, Meshkani Zahra2, Moosavi Nejad Seyed Masood3, ValipourYekani Neda4* 1. MSc of Health Economics, Social Determinants of Health Research Center, Shiraz University of Medical Sciences, Shiraz, Iran 2.  Ph.D. Student in Health Economics, Health Management and Economics Research Center, Iran University of Medical Sciences, Tehran, Iran 3. M.D, Ph.D. Student in Health Service Management, Faculty of Science and Technology, Sciences & Research Branch, Islamic Azad University, Tehran, Iran 4. MSc in Health Service Management, Faculty of Public Health, Tehran University of Medical Sciences, Tehran, Iran *Correspondence: Department of Management and Economics, Faculty of Public Health, Tehran University of Medical Sciences, Poursina Street, 16 Azar Street, Enghelab square, Tehran, Iran Tel: 00982138244274                                               Email: nedavalipour9@yahoo.com Abstract: Background & Objectives: Oral and dental disorders have a significant role in the development of diseases such as respiratory and cardiovascular diseases and diabetes. So prevention of oral and dental problems should be one of the most important health system priorities. On the other hand, the fair distribution of dentists for a full coverage of the whole country is not suitable. In this study, the distribution of dentists and their density in Fars province were investigated. Methods: In this descriptive study, population statistics of Fars Province,  as well as the number of active dentists in the public sector in each county in 2015 And 2016 were obtained from the Iranian Statistics Center and the Deputy of Health of Fars province. Finally, using the Gini and Robin Hood indices, the distribution of dentists was studied. Results: Gini index for dentists in 2015 and 2016 was calculated as 0.32 and 0.27, respectively, and 503 and 485 dentists had to be redistributed in order to achieve a complete equality. Accordingly, the number of dentists in the city of Shiraz should be reduced in order to be redistributed in other cities.  Conclusion: Health care policy makers should distribute dentists in different parts of the country according to their needs and based on the extent of deprivation of the areas, the success rate of past interventions in maintaining human resources, and the increasing or decreasing trend of the Decay-missing-filled teeth index in recent years.   Keywords: Dentists, Equal distribution, Redistribution, Service benefits, Gini index, Robin Hood index   Citation: Moalemi S, Meshkani Z, Moosavi Nejad SM, ValipourYekani N. Inequality in Distribution of Human Resource in Health Sector: Case Study of Dentists in Fars Province. Journal of Health Based Research 2018; 4(3): 261-72. [In Persian]